An alternative Japan experience. (11th October 2018) - Davis, Brett
Kanazawa, on the Japan Sea Coast, is one city that most international researchers visiting the country never see and might make an attractive destination for scientists. Kanazawa, on the Japan Sea Coast, is one city that most international researchers visiting the country never see and might make an attractive destination for scientists.